Knowledge, experience and perceptions regarding Molar-Incisor Hypomineralisation (MIH) amongst Australian and Chilean public oral health care practitioners. Issue 1 (December 2016) - Gambetta-Tessini, K.; Mariño, R.; Ghanim, A.; Calache, H.; Manton, D.
Abstract Background Molar-Incisor Hypomineralisation (MIH) is a prevalent developmental defect of tooth enamel associated with a high burden of disease. The present study aimed to survey Australian and Chilean oral health care practitioners (OHCPs) working in public dental facilities and to compare their knowledge, clinical experience and perceptions about MIH. Findings would give insights about how current knowledge has penetrated into OHCPs working into the public systems. Methods A mixed-mode survey regarding MIH was carried out amongst Australian and Chilean OHCPs from the public sector. The survey required responses to questions regarding sociodemographics, clinical experience, perceptions, clinical management and preferences for further training. The level of knowledge regarding MIH was determined by Delphi methods for consensus. Data analysis utilised Chi-square, linear and logistic regression models using SPSS Ver. 22.0. Results The majority of respondents had observed MIH in their patients (88.6 %) and the level of knowledge regarding MIH was high in Australian participants (p  = 0.03). Australian respondents felt more confident when diagnosing (OR 8.80, 95 % CI 2.49–31.16) and treating MIH-affected children (OR 4.56, 95 % CI 2.16–9.76) compared to Chilean respondents. Oral health therapists reported higher levels of confidence than Australian general dental practitioners when providing treatment to children with MIH (OR 7.53; 95 % CI 1.95–29.07). Conclusions Continuing to update clinical guidelines may help practitioners increase their understanding when diagnosing and treating MIH-affected children. Dissemination of information and awareness regarding MIH is necessary in public clinics, and in particular Chilean general dental practitioners should be alerted to these factors.